Signifikansi Pengaruh Sentimen Pemberlakuan PSBB terhadap Aspek Ekonomi: Pengaruh pada Stock Return dan Nilai Tukar Rupiah (Studi Kasus Pandemi Covid-19) - Erika Tri Siti Hidayah; Rr Tjahjaning Poerwati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to further analyze the effect of sentiment on the implementation of PSBB on stock returns and the rupiah exchange rate. The sample of this study was determined by the purposive sampling method based on the criteria of companies listed on the Indonesian stock exchange during the 2020-2021 period and companies that are members of bluechip stocks during the 2020-2021 period. This research uses multiple linear regression model. The results of this study conclude that the sentiment of the application of PSBB has a significant effect on the exchange rate but has a significant negative effect on stock returns.